Foreign direct investment and the risk of expropriation - Jonathan P. Thomas; Tim Worrall (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Foreign direct investment accounts for a considerable proportion of international capital flows. In 1986 the flow of foreign direct investment from developed market economies to developing countries was 12.5 billion or roughly one-half of all private capital flows from the developed to the developing nations (and roughly one-quarter of the flow of all foreign direct investments). Its significance for developing countries may even grow in the future as debt is swapped for equity (see Pollio and Riemschneider, 1988). The most important sector in volume term is the manufacturing sector, the concern of this paper. In 1978 total stocks of manufacturing foreign direct investment accounted for roughly two-thirds of the total in less developed countries, with just one-eighth devoted to the extractive industries (see Stopford and Dunning, 1983, p.22).
Keywords: 330